Survei Tingkat Kebugaran Jasmani pada Atlet Perkumpulan Bulutangkis Kapuas Jaya Kabupaten Kapuas - Nabella Pebriani, Laili (Pendidikan Jasmani, Kesehatan, dan Rekreasi, 2022)
Physical fitness is an important factor that must be considered by every athlete, where physical fitness can greatly affect the performance of his game. The better a person's physical fitness level, the higher his physical work ability. This study was conducted to determine the level of physical fitness of athletes PB Kapuas Jaya. This research is a quantitative descriptive study with a survey method. The instrument used in this study was the 2.4 km cooper test. The population in this study were athletes from PB Kapuas Jaya, Kapuas Regency, totaling 40 athletes. Based on the results of the study, it can be concluded that: The level of physical fitness of the athletes of the Kapuas Jaya badminton association, Kapuas district is in the